Status Demotion in Hierarchical Loyalty Programs: Effects of Payment Source - Ramaseshan, Balasubramani; Stein, Alisha; Rabbanee, Fazlul (Routledge, 2016)
Hierarchical loyalty programs are being operated currently by many firms to improve customer relationships. While past work has demonstrated the negative effects of status demotion in such programs, research on how these effects may vary across different customer group based on payment source is almost nonexistent. This paper examines the moderating role of payment source (‘own money’ versus ‘others money’) on the effects of status demotion on customer attitudes and behavior in hierarchical loyalty programs. Analysis of data collected from members of airline loyalty programs show that the negative effects of status demotion on customer attitudes, loyalty intentions, and share-of-wallet are stronger for demoted ‘own money’ customers than for demoted ‘others money’ customers. The study provides a deeper insight about the effects of status demotion and points out that firms could possibly be endangering the loyalty of many potentially valuable customers, in particular among the ‘own money’ customer group.